A case of bilateral recurrent exudative pleural effusion in a post COVID patient (Bangladesh Journal of Medicine, 2021)
COVID-19-related pleural effusions are frequently described during the ongoing pandemic. Pleural effusions result from the accumulation of fluid in the pleural space surrounding the lungs. The most common causes of bilateral pleural effusions are due to congestive cardiac failure, nephrotic syndrome, anasarca due to any protein deficiency state or fluid overload, hypothyroidism. Few exudative causes of bilateral pleural effusion also like tuberculosis, primary and metastatic pleural malignancy, bronchogenic Ca, lymphomas, Immunological diseases: Mixed connective tissue disease, long standing cardiac failure or liver failure (on diuretics). Exudative causes of bilateral turbid pleural effusion with recurrent accumulation are very rare without any other associated pathology. The significance of pleural effusions in COVID-19 pneumonia has not been well assessed due to the rarity of the disease limited to case reports/series. A 72-year-old male patient comes to emergency with the complaints increasing shortness of breath for 3 days, Dry cough for same duration, H/O of COVID pneumonia 2 months back with no other comorbidity. A chest computer tomography (CT) radiograph revealed a bilateral pleural effusion, which was further assessed as exudative type. Pleural fluid study reveals exudative hemorrhagic turbid fluid with ADA 71.5 U/L with neutrophilicleukocytosis. Pleural fluid culture reveals moderate growth of pseudomonas species with scanty growth of Candida species. The patient was diagnosed as a case of bilateral complicated recurrent parapneumonic effusion and treated with antibiotic as culture sensitivity with steroids. After 4 times aspiration paracentesis patient was discharged with minimal bilateral pleural effusion. The patient has been followed for 4 months and now he is doing well.Bangladesh J Medicine July 2021; 32(2) : 149-155